Effects of Nurse Navigators During the Transition from Cancer Screening to the First Treatment Phase: A Systematic Review and Meta-analysis - Oh, Jiwon; Ahn, Sukhee (Asian nursing research, 2021)
Implementation of nurse navigators during cancer screening to the first treatment visit may facilitate early diagnosis and treatment. This study aims to demonstrate the evidence of the effects of nurse navigators during cancer screening in the first treatment phase. Eleven electronic databases were searched, including PubMed, CINAHL, Cochrane Central Register of Controlled Trials (CENTRAL), EMBASE, Web of Science, ScienceDirect, PsycINFO, KoreaMed, KISS, RISS, and DBPIA. The final search was completed in August 2021. Two reviewers independently screened and selected studies, extracted data, and conducted a quality assessment. Data to evaluate the effects of nurse navigators was analyzed through meta-analysis and narrative summary. Subgroup analyses were performed. A total of 16 studies was included. With low to moderate quality of evidence, nurse navigators had favorable effects on improving the timeliness of care during screening during the first treatment visits (MD = 20.42, 95% CI = 8.74 to 32.10, p = .001). Additionally, 13.0% to 45.0% of nurse navigated patients were more likely to complete cancer care services, although insignificant effects were observed. Study participants from individual studies reported a high satisfaction to the nurse navigators. Subgroup analyses indicated that nurse navigators working as key members in multidisciplinary programs had the greatest effect on reducing waiting times. Nurse navigators improve cancer patient outcomes by providing more timely care. Additionally, nurse navigators have the substantial potential to increase completion rates to cancer care services and patient satisfaction. For facilitating multidisciplinary care, the use of nurse navigators is highly recommended in the future.